THE EFFECT OF INFORMATION TECHNOLOGY, ORGANIZATIONAL COMMITMENTS, AND INTERNAL CONTROL SYSTEMS ON VILLAGE FUND MANAGEMENT ACCOUNTABILITY - Alfina Ebrianty; Dianita Meirini (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2022)
This study aims to examine the effect of the variables of using information technology, organizational commitment, and internal control systems on the accountability of village fund management partially and simultaneously. This research uses quantitative methods. Determination of the sample using a non-probability sampling technique with criteria for village officials who serve as village heads, village secretaries, heads of financial affairs, heads of planning affairs, heads of administrative and general affairs, heads of government sections, heads of welfare sections, and heads of service sections. The data used in the form of primary data by distributing questionnaires using a Likert scale to 122 village officials. The statistical methods used are data quality test, multiple linear regression analysis, classical assumption test, and hypothesis testing with the help of the IBM SPSS 25 application. From the results of this study, it was found that the use of information technology and internal control systems partially had a positive and significant effect on village fund management accountability, while organizational commitment partially did not have a positive effect on village fund management accountability. Based on the F test, it was found that the use of information technology, organizational commitment, and the internal control system simultaneously had a positive and significant effect on the accountability of village fund management.